Anterior Tooth Size Discrepancy in Class III Surgical Patients - Ezgi Sunal Aktürk; Özge Müftüoğlu; Tülin Ufuk Toygar Memikoğlu (Galenos Yayinevi, 2022)
Objective:The purpose of the present study was to specify whether there are mesiodistal tooth size discrepancies in the anterior region in patients with dentoskeletal Class III malocclusion who underwent orthognathic surgery and orthodontic treatment and to assess the relationship between anterior Bolton ratio and dentoskeletal cephalometric measurements.Methods:The diagnostic dental casts and lateral cephalometric radiographs of 113 nongrowing patients (54 females and 59 males; mean age: 19.96 ± 4.42 years) with dentoskeletal Class III malocclusion who underwent orthognathic surgery and orthodontic treatment were included in the study. The mesiodistal widths of the 6 anterior teeth were measured from dental casts using a digital caliper accurate to 0.01 mm and anterior Bolton ratios were calculated. Lateral cephalograms were digitalized and used to measure 4 skeletal and 4 dental parameters.Results:The mean anterior ratio of Class III surgical patients was 80.1% with a standard deviation of 2.8%. Clinically significant anterior tooth size discrepancies (greater than ±2 standard deviation) were found in 40.7% of the sample, 97.8% of those patients having anterior mandibular tooth excess. No significant correlation was found between the anterior Bolton ratio and cephalometric measurements.Conclusion: Clinicians should consider the probability of tooth size discrepancy in the diagnosis and treatment planning of Class III surgical patients and should perform interventions to eliminate these discrepancies during presurgical orthodontic treatment.